Study on behaviour of concrete added with different length of bamboo fibres - Ting, Li Chao (2015)
Nowadays, concrete is highly contributed in the construction works for its various advantages such as low cost, availability, fire resistance and others. Generally, concrete is high in compressive strength but relatively low in tensile strength. Steel is the mostly used for the reinforcement of concrete due to its high tensile strength. Alternate materials such as fibres are used to increase the tensile strength of the concrete. Bamboo is natural, cheap and readily available material. Most importantly, bamboo has a high tensile strength. This research is aimed at studying the performance of concrete with bamboo fibres as additives in it. The objective of this research was to experiment the structural behaviour of bamboo fibres reinforced concrete (BFRC) with various length of bamboo fibres as additives. In this paper, 2% of bamboo fibres by volume of the concrete with the length of 40mm and 60mm are added into concrete and compare with the plain concrete which act as the control specimen. 2 tests are tested which are the cube compression test and flexural test. From the test result has shown that the compressive strength of different length of BFRC is lower as compared to the controlled cube specimen. For flexural strength, the 40mm BFRC is the most optimum length as it has shown the almost similar strength with the controlled beam specimen. The flexural strength for the 60mm BFRC is slightly lower than that of the controlled beam specimen.